Comman errors in pronouncing arabic phonetic among malaysian students in debate - Paharal Radzi, Majdan; Mezah, Che Radiah; Mustapha, Nik Farhan; Aziz, Mohammad Azizie (Pusat Kembangan Kolej Universiti Islam Sultan Azlan Shah, 2015)
There is no doubt that Arabic Language learners, specifically the debaters, should have the appropriate phonetic skills and be competent in their performance of this language. Therefore, this study attempts to identify common errors in pronouncing Arabic phonetic among Malaysian students in debate. This study uses the qualitative analysis in describing the elements of presentation styles. Respondents were selected from the University of Sultan Zainal Abidin (UniSZa) and the International Islamic University of Malaysia (IIUM). Support data were also collected from two experts interviewed in the study. The results of the study show that some Arabic consonants should be paid more attention to including Ha, Ain, Qaf, Tha, Dhad, Kha and Sad.